Digi-flash pedagogy confronts new emerging technologies - Maturity level evaluation case study. Issue 1 (31st December 2023) - Liljaniemi, Antti; Paavilainen, Heikki; Tuominen, Timo
Abstract: There is significant interest in emerging technologies. Universities, companies and other adopters are researching how and when these technologies should be implemented. However, this research area still lacks ways to evaluate the maturity level of the technologies and rapid experimentation concepts for testing the new technologies. This paper addresses the research gap by providing a new evaluation method and a rapid experimentation concept. This method and concept were successfully used in twenty-five Flash-projects, where five emerging digital Industry 4.0 themes evaluated.